A group‐specific sequence‐based typing approach for HLA‐DQA1. (24th December 2014) - Lemin, A. J.; Johnson, J.; Darke, C.
Summary An HLA‐DQA1 sequence‐based typing method reliant upon group‐specific amplification to achieve an unambiguous second‐field DQA1 typing assignment is presented. Method validation, using 51 reference DNA samples covering 21 different DQA1 alleles, showed 100% concordance with the reference types. This typing strategy has several important uses including identifying DQA1 mismatches in kidney donor/recipient pairs to inform patient DQ antibody assignments.